I want Mathematica to recognize that
A.(-B.C)+A.B.C = 0
Yet FullSimplify and the like leaves the expression as it is. How do I get around this?
Check the tutorial here.
a.(-b.c) + a.b.c // TensorExpand
(* ==> 0 *)
You can teach Mathematica to factor out any number from inside a dot.
x__.(c_?NumberQ y__) := c x.y
(c_?NumberQ x__).y__ := c x.y
Sign up using Google
Sign up using Facebook
Sign up using Email and Password
3 years ago
Get the weekly newsletter! In it, you'll get:
see an example newsletter